Feeding fresh food and providing water ad libitum is clinically proven to exceed calculated daily water requirements and impact urine relative supersaturation in dogs - Sires, Rae; Yamka, Ryan; Wakshlag, Joe (Frontiers in Veterinary Science, 2025)
A series of studies were conducted to evaluate a fresh food for its impact on total water consumption compared to a dry or canned pet food and urine relative supersaturation in healthy adult dogs. Study 1: Ten dogs were used in a single cross-over study design to quantify and compare feeding a fresh food (71.1% moisture) versus a dry kibble food (6.1% moisture) on total daily water consumption (drinking + food moisture). Dogs consuming the fresh food consumed more food by weight on an as-fed basis (+348 grams; p < 0.0001), but less on a dry matter basis (−17 grams; p < 0.0001). Dogs fed the dry food consumed more water ad libitum (+276 grams; p < 0.0001) when compared to the fresh test food group, however dogs consuming the fresh food consumed significantly more total water daily on average per day (+88 grams; p < 0.0001). Dogs consuming the fresh food far exceeded their minimum water requirement compared to the dry food (141% vs. 102%; p < 0.0001). Study 2: Ten dogs were used in a single cross-over study design to quantify and compare feeding a fresh food (71.1% moisture) versus a retorted canned food (75.1% moisture) on total daily water consumption. The mean daily food consumption was statistically significantly higher for the dogs consuming the canned food compared to the fresh food (497 grams compared to 461 grams; p < 0.05). The total water intake of the canned food group was significantly higher than dogs fed the fresh control food (p < 0.05), however, all dogs had total water intakes well above 100% of their calculated water requirement. Study 3: Ten adult dogs were used to evaluate urine relative supersaturation; the mean for struvite was 0.203 ± 0.105 and the mean for calcium oxalate was 1.784 ± 2.660. In conclusion, fresh food can impact urine relative supersaturation and help support hydration in healthy adult dogs or those that are at risk of dehydration and water loss.